Partitioning of Dry Matter in Finger Millet (Eleusine coracana L. Gaertn.) under Different Establishment Techniques, Levels and Time of Application of Nitrogen - CHAVAN, I B; JAGTAP, D N; MAHADKAR, U V (Journal of the Indian Society of Coastal Agricultural Research, 2019)
A field experiment was conducted to study the effect of establishment techniques, levels and time of application of N on partitioning of dry matter in finger millet (Eleusine coracana L. Gaertn) under lateritic soils of Konkan. The total 48 number of treatment combinations consisted of four techniques of establishment as main plots (T1- Recommended transplanting at 20 cm x 15 cm, T2- Random transplanting, T3- Random broadcasting of 30 days old seedling (Awatni), T4- Random broadcasting of 20 days old seedling (Awatni), three N levels in sub plots (F1- 60 kg N ha-1, F2- 80 kg N ha-1, F3- 100 kg N ha-1) and four kinds of N application as sub-sub plots (S0- Basal (half dose through suphala (15:15:15)), S1- 2 Split applications: one at transplanting and second at 30 days after transplanting (DAT), S2- 3 Split applications: one at transplanting, second at 30 DAT and third at 60 DAT, S3- 4 Split applications: one at transplanting, second at 20 DAT, third at 40 DAT and fourth at 60 DAT). Leaf and stem dry matter accumulation per hill were significantly enhanced due to recommended transplanting at all the growth stages except at initial period. Application of 100 kg N ha-1 recorded maximum and significantly higher values of leaves and stem dry matter accumulation per hill over rest of the N levels. Leaf and stem dry matter accumulation per hill were significantly enhanced due to three splits of N application (one at transplanting, second at 30 DAT and third at 60 DAT) during all the growth stages except at 20 DAT. From the investigation it can be concluded that to obtain higher grain and straw yield the finger millet crop should be established following the recommended transplanting at 20 cm x 15 cm and supplied with 100 kg N ha-1 in three equal splits (33.3% each at transplanting, 30 DAT and 60 DAT, respectively).